A Facile Method for Preparation of Tailored Scaffolds for DNA‐Origami. Issue 1 (17th July 2013) - Erkelenz, Michael; Bauer, Dennis M.; Meyer, Rebecca; Gatsogiannis, Christos; Raunser, Stefan; Saccà, Barbara; Niemeyer, Christof M.
<x xml:space="preserve">Abstract</x> A convenient PCR cloning strategy allows one to prepare hundreds of picomoles of circular single‐stranded DNA molecules, which are suitable as scaffolds for the assembly of DNA origami structures. The method is based on a combination of site‐directed mutagenesis and site‐ and ligation‐independent cloning protocols, with simultaneous insertion of a nicking endonuclease restriction site on a double‐stranded plasmid of desired length and sequence. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>